2001
DOI: 10.1542/peds.107.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Findings on Cranial Ultrasound and Magnetic Resonance Imaging in Preterm Infants

Abstract: US accurately predicted the presence of GLH, IVH, and hemorrhagic parenchymal infarction on MRI. However, its ability to predict the presence of DEHSI and small petechial hemorrhages in the WM on T2 weighted images is not as good, but improves on scans performed at >/=7 days after birth. In addition, normal WM echogenicity on US is not a good predictor of normal WM signal intensity on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
227
1
16

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(256 citation statements)
references
References 31 publications
6
227
1
16
Order By: Relevance
“…Nevertheless, previous authors, using 7.5-MHz transducers, also reported that most lesions of the basal ganglia and thalamus seen on neurosonography did not have CT or MRI correlates. 16,29 Third, there was not sufficient follow-up data in patients and controls to permit a valid analysis. Our study suggests that diffuse BGTH is not associated with anomalies of local cerebral blood flow pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous authors, using 7.5-MHz transducers, also reported that most lesions of the basal ganglia and thalamus seen on neurosonography did not have CT or MRI correlates. 16,29 Third, there was not sufficient follow-up data in patients and controls to permit a valid analysis. Our study suggests that diffuse BGTH is not associated with anomalies of local cerebral blood flow pattern.…”
Section: Discussionmentioning
confidence: 99%
“…More commonly, diffuse WM abnormalities are present in early preterm infants, with up to 79% of infants showing magnetic resonance imaging (MRI) abnormalities in WM (2). Through a number of MRI studies it has been shown that classical PVL does not represent the only features of preterm brain injury (3).…”
mentioning
confidence: 99%
“…More recent neuroimaging technology has demonstrated that in addition to periventricular/intraventricular hemorrhage and periventricular leucomalacia, there is a more diffuse non-cystic white matter involvement, sometimes associated with ventriculomegaly, that is present in 20 to 50% of very low birth weight infants, and is also associated with neurodevelopmental compromise. 446,[448][449][450][451] A magnetic resonance imaging study of a small group of premature infant between 28 to 33 weeks gestation, without ultrasonographic evidence of neurologic injury, found they still had a loss of white matter volume, but with a relative increase in grey matter volume. 452 In addition to the vulnerability of cerebral white matter in premature infants, there appears to be evidence that cerebral neuronal structures are also affected.…”
Section: Discussionmentioning
confidence: 99%